Arterial Hypertension And Its Early Diagnosis (Texas Journal of Medical Science, 2025)
Arterial hypertension (AH) is one of the leading causes of death and disability worldwide. This disease leads to damage to the cardiovascular system, significantly increasing the risk of myocardial infarction, stroke, heart failure and chronic kidney disease. Studies conducted in recent years have shown that even blood pressure above 115/75 mmHg begins to increase the risk of cardiovascular complications. Therefore, early diagnosis of arterial hypertension, that is, its detection and control in the early stages of the disease, remains one of the urgent scientific and clinical issues